House price determinants: a Malaysian cases / Nur Nadhirah Harmi - Harmi, Nur Nadhirah (2014)
According to Maslow's, everyone in this world has a hierarchy of need to fulfill on. The basic need for them is a shelter. Basically, a shelter will provide to anyone a protection from cold, hot, harm or danger. Rapid economic development has resulted in an increasing demand from residential property among urban areas in Malaysia. The increasing demand of house/residential property may be caused by any factors which may be come from qualitative factor or quantitative factors.